2020
DOI: 10.25046/aj0506147
|View full text |Cite
|
Sign up to set email alerts
|

Creativity in Prototypes Design and Sustainability – The case of Social Organizations

Abstract: The role of creativity techniques in the design of prototypes is of particular interest given its potential for innovation. At same time, despite the efforts of decades in terms of policies and programs of action, humanity has not yet come close to global sustainability. Sustainability design must involve society and creatively employ all available knowledge sources for creating sustainable software. This paper proposes a prototype design approach rooted in employing creativity techniques, while being guided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The areas involved in studying the various valences supported by a comprehensive strategy were analyzed, namely: physical therapy, social situation, medical care, nursing care, housing, experience, skills, health, training, and volunteering (Silveira, Reis, Santos, & Mamede, 2020b).…”
Section: Case Studymentioning
confidence: 99%
“…The areas involved in studying the various valences supported by a comprehensive strategy were analyzed, namely: physical therapy, social situation, medical care, nursing care, housing, experience, skills, health, training, and volunteering (Silveira, Reis, Santos, & Mamede, 2020b).…”
Section: Case Studymentioning
confidence: 99%
“…Engineering stands as a field in which the application of critical pedagogy can be particularly beneficial for students, given that it is a profession with a very clear civic vocation, in so far as its final aim is to respond to collective needs across a wide range of areas within society (Silveira et al, 2020;Kivimäki et al, 2023). Those areas range from proper management of a continuous supply of food, water, and electricity, to the design and the provision of goods, housing, and infrastructure (Revilla-Cuesta et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of sustainability is increasingly recognized, but the broader impacts of software systems on sustainability are still unknown. It is important to mention that some case studies have shown that the inclusion of sustainability factors since the beginning of the process is an asset and promotes the Sustainable Development Goals (Reis, Silveira, Carvalho, & Mata, 2020;Silveira, Reis, Santos, & Mamede, 2020;.…”
Section: Introductionmentioning
confidence: 99%